Multi-omics reveals glutinous rice varieties shape Baijiu flavor via microbial and metabolic modulation - Zeng, Jia; Gong, Lijuan; Qin, Shuai; Fang, Pengpeng; Shu, Fu; Zhang, Wuhan; Zhou, Yi; Li, Xinpeng; He, Qiang; Sun, Pingyong; Deng, Huafeng (Frontiers in Microbiology, 2026)
IntroductionGlutinous rice significantly influences Baijiu flavor, yet standardized brewing-specific indicators are lacking.MethodsIn this study, metagenomic, metaproteomic, and non-targeted GC–MS analyses of Zaopei, along with HS-SPME-GC–MS analysis of Baijiu, were used to compare the effects of three glutinous rice varieties with distinct nutritional profiles on microbial diversity and flavor formation.ResultsThe Wuliangye-specific variety Dajiugu, with high sucrose, high amino acids, and low fatty acids, promoted early growth and metabolic activity of Saccharomycopsis, Enterobacter, and Klebsiella. Functional genera such as Saccharopolyspora, Pediococcus, and Clostridium enhanced fatty acid and amino acid accumulation in Zaopei and increased ethyl acetate, 4-vinylphenol, and dimethyl trisulfide in Baijiu.DiscussionThese findings highlight the pivotal role of glutinous rice variety in shaping Baijiu flavor and offer a scientific basis for breeding brewing-specific glutinous rice.